GEOCHEMICAL FEATURES OF EARTH MINERALIZATION IN BLACK SHALES OF NORTHERN NUROTA RIDGE (ON THE EXAMPLE OF THE USTUK ORE OCCURRENCE) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
With the development of science and technology and the increasing demand for high-tech materials, the need for new raw materials such as rare earth elements (REEs) is rising. To create and enrich the base of REEs, the Ministry of Geology and Mining Industry of the Republic of Uzbekistan is encouraging the search for industrial mineralization of these raw materials in several promising areas. In the black shales of the Central Kyzylkum, particularly in the Northern Nurota ridge, numerous associations of uranium, molybdenum, and vanadium have been studied. Recent exploration and scientific research by several scientists, such as A.A. Khalilov and I.B. Turamuratov, have identified and are studying the relationship between uranium-vanadium-molybdenum mineralization and REE mineralization. This article presents the results of studies of the geochemical properties of these critical metals at the Ustuk ore occurrence.